Metal–organic framework nanosheets (MONs): a new dimension in materials chemistry. Issue 34 (17th August 2018) - Ashworth, David J.; Foster, Jonathan A.
Abstract : Metal–organic framework nanosheets (MONs) are emerging as a novel class of two-dimensional materials. Here we critically review the distinct set of design principles, synthetic approaches, characterisation techniques and applications associated with this exciting new class of materials. Abstract : Metal–organic framework nanosheets (MONs) are emerging as a novel class of two-dimensional materials with a distinct set of design principles, synthetic approaches, characterisation techniques and applications. MONs are free standing, nominally two-dimensional materials formed by the co-ordination of organic ligands to metal ions or clusters. In comparison to other metal–organic and two-dimensional materials, the principles behind their design and synthesis are only just beginning to be understood. Here we seek to bring together recent highlights from this rapidly growing field and attempt to draw out common principles and strategies which we hope will aid the development of this exciting new class of materials. We consider the range of chemistries and different synthetic strategies used to fabricate MONs, the methods employed to characterise them and the applications that have so far been investigated.